2018
DOI: 10.1039/c8py01314d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of fluorescent conjugated polymer nanoparticles and their immobilization on a substrate for white light emission

Abstract: Fluorescent conjugated polymers (CPs) for blue, green, and red emission were polymerized via the Suzuki coupling reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…The absolute QY of the CPdot solution, CPdots immobilized glass, and CPdots immobilized nanofibers were determined as 20%, 24%, and 38%, respectively. [ 118 ] Li et al reported series of new polymers based on a methacrylate monomer containing a switchable boron chromophore, which displayed rare multicolor fluorescence in solution highly dependent on the degree of polymerization (DP). The local concentration of the chromophore increased with increasing DP, which led to a higher propensity for switching the blue‐emitting tricoordinate boron chromophore to the red‐emitting tetracoordinate.…”
Section: Recent Advances In Organic and Polymer Luminescent Materialsmentioning
confidence: 99%
“…The absolute QY of the CPdot solution, CPdots immobilized glass, and CPdots immobilized nanofibers were determined as 20%, 24%, and 38%, respectively. [ 118 ] Li et al reported series of new polymers based on a methacrylate monomer containing a switchable boron chromophore, which displayed rare multicolor fluorescence in solution highly dependent on the degree of polymerization (DP). The local concentration of the chromophore increased with increasing DP, which led to a higher propensity for switching the blue‐emitting tricoordinate boron chromophore to the red‐emitting tetracoordinate.…”
Section: Recent Advances In Organic and Polymer Luminescent Materialsmentioning
confidence: 99%
“…Strategies include: (i) precise molecular design and careful sequential control of intercomponent interactions in either solution or solid-state, 37 and (ii) partial isolation of the chromophores in a matrix to avoid redundant energy transfer. 38 Both of these methods are experimentally complicated and troublesome. We recognised that supramolecular gelators could be applied in this regard, as a special kind of dispersion system, containing a lot of liquid and showing both solid and solution properties.…”
Section: Introductionmentioning
confidence: 99%
“…Various approaches, such as single white light polymers [11,12], exciplex [13], multiple blending [14] and utilization of tandem device [15,16], have been reported to realize white emission. Thereinto, multiple blending should be the advisable means to achieve high CRI white emission considering the simple device structure especially for the solution processed.…”
Section: Introductionmentioning
confidence: 99%